About "Provisional" in Descartes' Provisional Morality and a Critical Review of Some Contemporary Readings - Mahdi Behniafar (حکمت و فلسفه, 2019)
This essay deals with Descartes' Provisional Morality and some of its epistemic requirements. Here, we shall introduce two rival readings of these principles, one of which does not give a plausible position to these principles and does not consider them to be an essential part of Descartes's system, and the other assumes these principles to be both permanent and universal, and then present our explanation to the epistemic realm and also the human realm of these principles. First, we have presented our account of the relation between these Maxims with Cartesian key elements, namely Doubt and Method. Then we discuss the basic nature of Provisionality of these Maxims; a concept that is apparently normal but has relatively different results and requirements. I argue that the moral code has an epistemic character, not a time; time also depends on the events of Reason. Also, while we argued that these principles cannot be considered temporary, we have shown that the idea of some Descartes commentators that these principles, from the very beginning, were permanent and universal is a misconception that can't be imposed on Descartes. Based on our argument, these principles can be transformed into permanent principles in certain epistemic conditions that we have explained, but at the same time, in certain circumstances, they may also be disaffirmed and, as a result, become temporary principles. When these maxims count as the product of an argumentative process, then a non-argumentative description such as the conservatism of these principles will be an abnormal description that is unrelated to Descartes' will.